(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ethnomedicine has always played an important role in the different ethnic groups of our society. Tribal people use their previous knowledges via their ancestors, books, or by any other medium to extract the different aspects of uses of different plants and their parts Ethnomedicinal study of common plants was done and also during authentication of plants species we noticed some endangered and vulnerable species. An ethno-medicinal documentation and study was done from April 2022 to August 2022to evaluate the exploration and preservation of different growing plants in Giridih District of Jharkhand, India. The present paper describe some ethnomedicinal plants of Jharkhand especially from Giridih district.